A first attempt at Problem-Based Learning (PBL): the experience with first-year undergraduates - Mustafa, Maizatun (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
This paper is based on a first-hand experience in implementing PBL for teaching Malaysian Legal System I for the first year undergraduates of the Ahmad Ibrahim Kulliyyah of laws, IIUM during semester 1 2004-2005. This PBL was a first attempt where previously the subject was taught using the conventional lecture-tutorial methods. However, it is emphasized that the PBL method applied here was more of a trial and error with many mistakes that may have been made along the way. This paper is thus about trials and tribulations of implementing a PBL method and the many practical difficulties and unexpected challenges encountered. The objective is to provide some insights that may be used by others attempting to implement PBL. It is in this spirit that this experience is shared.